Diminazene aceturate poisoning in a dog (Canis familiaris) treated for visceral leishmaniasis: pathological and toxicological evaluation - Silva, Nayara Toledo da; Nascimento, Acácia Eduarda de Jesus; Souza, Lucas dos Reis de; Soto-Blanco, Benito; Oliveira, Ayisa Rodrigues (Brazilian Journal of Veterinary Pathology, 2024)
A one-year-old Whippet dog with a prior diagnosis of visceral leishmaniasis was treated with diminazene aceturate with intramuscular and oral routes, developing acute neurological signs, and was necropsied after death. The necropsy revealed marked systemic congestion, multiple hemorrhagic foci, pulmonary edema, and hemorrhage and necrosis in the brainstem. Brain histopathology showed marked neutrophilic encephalitis with vascular fibrinoid necrosis and hemorrhage restricted to the brainstem. Liver and kidney samples were submitted for toxicological evaluation, revealing elevated levels of diminazene aceturate, corroborating with the diagnosis of poisoning. The pathological findings observed in this case are consistent with those described in the literature regarding diminazene aceturate poisoning. A diagnosis should be performed based on the animal’s clinical history, pathological findings, and the results of the toxicological examination.